Measurement of the B0s→[mu]+[mu]− branching fraction and effective lifetime and search for B0→[mu]+[mu]− decays - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Braun, Svende; Comerma-Montells, Albert; De Cian, Michel; Esen, Sevda; Gerick, David; Gersabeck, Evelina; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Kecke, Matthieu; et al. (Physical review letters, 2017)
A search for the rare decays B0s→μ+μ− and B0→μ+μ− is performed at the LHCb experiment using data collected in pp collisions corresponding to a total integrated luminosity of 4.4 fb−1. An excess of B0s→μ+μ− decays is observed with a significance of 7.8 standard deviations, representing the first observation of this decay in a single experiment. The branching fraction is measured to be B(B0s→μ+μ−)=(3.0±0.6+0.3−0.2)×10−9, where the first uncertainty is statistical and the second systematic. The first measurement of the B0s→μ+μ− effective lifetime, τ(B0s→μ+μ−)=2.04±0.44±0.05 ps, is reported. No significant excess of B0→μ+μ− decays is found, and a 95% confidence level upper limit, B(B0→μ+μ−)<3.4×10−10, is determined. All results are in agreement with the standard model expectations.